Analysis Of The Influence Of Economic Growth And Human Development Index On Poverty In Jombang District In 2012-2022: THE EFFECT OF ECONOMIC GROWTH AND THE HUMAN DEVELOPMENT INDEX (HDI) ON POVERTY - Naufal, M. Harisun; Fadhli , Khotim (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
Poverty can be defined as an economic inability to meet basic food and non-food needs as measured in terms of expenditure. To measure poverty, certain indicators are used, because indicators are indirect measurements of an event or condition, such as poverty. BPS has 14 indicators that can be used to measure poverty in Indonesia. These indicators can be grouped into three quality categories, namely economics, human resources (HR), and health. According to the Jombang Regency government's explanation on the Surabaya Morning page, the poverty rate in Jombang Regency could decrease below 8.5 percent. Based on the background of this problem, this research is intended to measure and analyze how economic growth and the human development index influence poverty in Jombang Regency. Economic growth shows that it does not have a significant influence on poverty in Jombang district in 2012-2022. This happens if an increase in growth will cause a decrease in poverty in Jombang Regency and conversely if there is a decrease in economic growth it will increase poverty. The human development index has a positive effect on the poverty variable with the regression coefficient value showing that the human development index has a positive effect on poverty in Jombang Regency in 2012-2022. If there is an increase in the level of human development, it will also increase the level of poverty, and conversely, if there is a decrease in the human development index, it will reduce poverty. Economic growth and the human development index both have an influence on poverty in Jombang Regency. If the economic situation improves, poverty will decrease, and if the high human development index is not equivalent to economic growth, the poverty level will increase. Various alternative economic solutions have been carried out, including the creation of RPJMDes, increasing MSMEs, and so on. Keywords: economic growth, human development index, poverty in Jombang district